2023
DOI: 10.1186/s40168-023-01593-z
|View full text |Cite
|
Sign up to set email alerts
|

Neotropical bee microbiomes point to a fragmented social core and strong species-level effects

Abstract: Background Individuals that band together create new ecological opportunities for microorganisms. In vertical transmission, theory predicts a conserved microbiota within lineages, especially social bees. Bees exhibit solitary to social behavior among and/or within species, while life cycles can be annual or perennial. Bee nests may be used over generations or only once, and foraging ecology varies widely. To assess which traits are associated with bee microbiomes, we analyzed microbial diversit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 56 publications
1
16
1
Order By: Relevance
“…We also detected the disparity in Wolbachia presence and abundance between social and solitary bees (Table 2), as previously described (De Ramalho et al, 2021;Gerth et al, 2011Gerth et al, , 2015. Further to this, our findings regarding the lack of "corbiculate core" microbes in Euglossini species has been reported since the analysis was undertaken (Kueneman et al, 2023).…”
Section: Mining Rna-seq Samples Recapitulates Experimental Findings I...supporting
confidence: 85%
See 1 more Smart Citation
“…We also detected the disparity in Wolbachia presence and abundance between social and solitary bees (Table 2), as previously described (De Ramalho et al, 2021;Gerth et al, 2011Gerth et al, , 2015. Further to this, our findings regarding the lack of "corbiculate core" microbes in Euglossini species has been reported since the analysis was undertaken (Kueneman et al, 2023).…”
Section: Mining Rna-seq Samples Recapitulates Experimental Findings I...supporting
confidence: 85%
“…However, the sample size for the Meliponini bees in this analysis was considerably smaller (n = 7), and yet, this core community was detectable. As this study was under review, Kueneman et al, 2023, also failed to detect a stable set of core microbes among orchid bee species, lending further weight to these findings. It should be noted, however, that their findings also suggested that the relationship between the "corbiculate core" and stingless bees also may not be as strong as previously theorised, suggesting a complicated picture that requires further investigation.…”
Section: "Corbiculate Core" Microbes May Be Specific To the Obligatel...mentioning
confidence: 61%
“…The highest mean of total abundance among all groups was in flower buds (8.22%), followed by 20 daf seeds (6.37%) and young pods (3.99%), and the lowest was in mature seeds (0.31%) ( Table S9 ). Notably, Neisseriaceae is one of the common families in pollinator microbiomes [ 69 , 70 ]. The above findings apply equally to Prevotella 1 and Prevotella 2 [ 69 , 71 ], which were also enriched in flower buds (4.62%), followed by young pods (1.62%), 20 daf seeds (1.59%), and found to be decreased in mature seeds (0.02%).…”
Section: Resultsmentioning
confidence: 99%
“…Notably, Neisseriaceae is one of the common families in pollinator microbiomes [ 69 , 70 ]. The above findings apply equally to Prevotella 1 and Prevotella 2 [ 69 , 71 ], which were also enriched in flower buds (4.62%), followed by young pods (1.62%), 20 daf seeds (1.59%), and found to be decreased in mature seeds (0.02%).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation